KAJIAN ETIKA PENGAMBILAN KEPUTUSAN ANTARA PELAKU BISNIS DAN KONSUMEN BERDASARKAN PERSONAL MORAL PHILOSOPHIES DAN ETHICAL PERCEPTIONS SELAMA SATU DEKADE ANTAR SUB-BUDAYA YOGYAKARTA DAN BALI - Diah Pradiatiningtyas - AMIK BSI Bandung; Sari Winahjoe Siswomihardjo - Universitas Gadjah Mada (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2012)
Ethical problems are arising among this decade, especially in marketing. In Indonesia ethical problems in organization also arise in this decade. Ethics is the discipline that deals with what is good and bad and with moral duty and obligation. Ethics can also be regarded as a set of moral principles or values. Morality is a doctrine or system of moral conduct. Moral conduct refers to that which relates to principles of right and wrong in behavior. Business ethics, therefore, is concerned with good and bad or right and wrong behavior that takes place within a business context. Concepts of right and wrong are increasingly being interpreted today to include the more difficult and subtle questions of fairness, justice, and equity. The aim of this paper was to integrate personal moral philosophies and ethical perceptions to business decision making. Two different sub cultures are present in this paper: Yogyakarta and Bali, which has identical sub culture. The conclusion of this literature review is decision making of organization and consumer can effect by personal moral philosophies and ethical perception. Bali has idealistic moral philosophies and Yogyakarta has relativism moral philosophies.   Keywords: Ethics, Personal Moral Philosophies, Ethical Perceptions, Decision Making